A phase 3, randomized, open-label, multicentre study to evaluate the efficacy and safety of diltiazem plus lidocaine fixed-dose combination gel versus diltiazem gel in Indian patients with anal fissure - Mital, Kushal; Babu, Naga; Patel, Apoorva; Jauhari, R. K.; Mohan, Sanjeev; Basu, Indraneel; Acharya, Shivani; Verma, Rajan; Karankumar, Jejoe (International Journal of Research in Medical Sciences, 2025)
Background: Anal fissures cause significant pain and morbidity, requiring prompt and effective treatment. This study aims to evaluate the efficacy and safety of a fixed-dose combination (FDC) gel containing diltiazem and lidocaine compared to diltiazem gel alone in the treatment of anal fissures. Methods: In this randomized, open-label, phase 3 study, eligible Indian patients (n=326) of either sex, aged 18 to 64 years, were randomly allocated (1:1) to the test (FDC diltiazem and lidocaine) or reference (diltiazem) group. Patients were asked to apply 1 g of test or reference product, intra-anally, thrice-a-day, for 40±2 days. The assessment time points were day 1, 5, 10, 25, and 40. Results: There was a significant reduction in pain scores between the test group and the reference group at the assessment time points. The least-squares mean difference in the mean anal pain intensity reduction from Baseline to day 10 between test and reference groups was ─.1 (95% confidence interval: ─9.18, ─3.02; p=0.0001). More patients in the test versus reference group had pain relief at 0.5 hours after first treatment application on day 1 (60.7% versus 48.8%; p=0.0302). Proportion of patients with partial healing of anal fissure was significantly higher at day 5 (64.2% versus 46.5%; p=0.0015) and day 10 (92.5% versus 81.5%; p=0.0036) in the test versus reference group) treatment-emergent adverse events occurred in four patients in the test group and in eight patients in the reference group. Conclusions: In this large, phase 3 multicentric study, the FDC of diltiazem and lidocaine demonstrated superior pain intensity reduction and early onset of pain relief with an acceptable safety profile as compared with diltiazem gel alone in Indian patients with anal fissure.